„Powinności” nauczyciela ludowego doby zaborów w przekazie czasopisma „Szkoła” - Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2020)
The aim of the article is to analyse the pedeutological texts published in the era of the Partitions of Poland in the pages of the oldest Galician pedagogical periodical, which “Szkoła” was. The journal, edited by teachers and educational activists, addressed mainly to folk school teachers, published uninterruptedly for 70 years, is for today’s researchers an invaluable source of knowledge about the functioning of Galician education and its employees. The editors and collaborators of the journal often took up such important subjects as vocation, role models of folk teachers, relations with pupils’ family homes or difficult realities of teacher’s work. Teachers received a lot of specific advice concerning the upbringing and education of pupils, frequently from older and experienced colleagues. They could also learn a catalogue of traits and attitudes expected from folk teachers, concerning also their own families or taking up additional work.